Theory, law and practice of maritime arbitration the case of international contracts for the carriage of goods by sea - Litina, Eva (International arbitration law library ;, 2021)
'Theory, Law and Practice of Maritime Arbitration' is a book that delves deep into the phenomenon of maritime arbitration with a specific focus on contracts for the carriage of goods by sea. The author furnishes the first comprehensive and comparative analysis of arbitral practice in the three jurisdictions where the most frequently selected maritime arbitral seats are located: London, New York, and Singapore. It is estimated that over 80% of global trade by volume is carried by sea, making maritime transport the backbone of the global economy. Most disputes in the shipping industry are settled by distinctive, private, mystery-enshrouded arbitral proceedings that are best understood by a close examination of the standard form contracts that are used in practice and of the case law arising therefrom. An in-depth analysis of the applicable rules and relevant case law in each jurisdiction provides the basis from which a comparative assessment of maritime arbitral seats is achieved.